Utilização de cenários aplicados à logística reversa de recuperação de ativos: destroca de vasilhames vazios das empresas distribuidoras de gás liquefeito de petróleo - Firmeza, Ozéias da Silva (2007)
The logistic programming of the companies of liquefied petroleum gas (LPG) is an important stage and basic in the process of planning of operation and, currently, its effectiveness the profitability and the survival depend on these companies. This because the market of LPG distribution has the peculiarity to possess profit edge very low and for more than to have in its raw material responsible 70% (seventy percent) of its cost. Thus, the companies of this branch have beenforced to be each time more efficient in its politics of costs, since the consuming market does not support more the view of these expenses, exactly if treating to a basic good. The related logistic programming does not deal with only the routes to be fulfilled for the trucks and yes the form that the logistic flows happen. This research has the purpose to study the logistic flow that occurs in the canal reverse, that is, the return of the empty containers the base of production to be again planted. The methodology used in this work is based on the construction of Scenes and to compare them enters itself and with what currently it is used by the company in study. The data raised in the related company will serve to validate the Scenes considered, and thus to serve to subsidize the logistic sector of the company taking decisions on optimum model of flow in the canal reverse, reducing costs and becoming the more efficient load movement in the urban environment. The considered scenes also will be evaluated how much to itsdegree of feasibility and its implications.